STATE, MARKET AND SOCIETY UNDER DISCUSSION: Between neoliberalism and socio-environmentalism as a development model - Silva, Thiago Henrique Costa; Gonçalves Neto, João da Cruz (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2024)
This academic essay aims to understand the relation between the State, society and the market, as well as its implications for the construction of the right to development in the world and in Brazil. After some considerations about the fundamentals of the Liberal State, the Social State and the Neoliberal State, we seek to critically elucidate whether the Brazilian model is close to neoliberal or socio-environmental development practices. In order to do that, bibliographic and documentary researches were carried out, guided by historical and dialectical methods, in a qualitative approach. Thus, it appears that the socio-environmental conception, centered on social, political, ethical and environmental values, prevails, legally, as a basis for thinking about development in the country.